Brief Overview on the Fabrication of Light-Emitting Diode (LED) Device via High and Low-Cost Techniques - Mohammad, Sabah M. (2020)
Why wight LEDs? With 20% of the world's electricity used for lighting, it's been calculated that optimal use of White LED lighting could reduce this to 4%. The use of a White LED will reduce the release of CO2 into the atmosphere by a significant amount. White LEDs are Energy efficient. Long life (A typical White LED lamp can last for 100,000 hours).